El servicio integrado de seguridad ECU-911 Machala y la correlación con los organismos de la función judicial de el cantón Machala, en el manejo de audios y vídeos como pruebas de cargo y descargo año 2013. - Espinoza Ortiz, Emma Carolina (2014)
The due process embodied in the constitution of the republic recognizes people’s right to have the test to demonstrate its responsibility in a criminal act is obtained in compliance with the constitution and the law, allowing it to be controversial in order to achieve its probative.